Virtual screening using docking and molecular dynamics of cannabinoid analogs against CB1 and CB2 receptors. (December 2021) - Aviz-Amador, Antistio; Contreras-Puentes, Neyder; Mercado-Camargo, Jairo
Abstract: Background: Cannabis sativa has been attributed to different pharmacological properties. A number of secondary metabolites such as tetrahydrocannabinol (THC), cannabinol (CBD), and different analogs, with highly promising biological activity on CB1 and CB2 receptors, have been identified. Methods: Thus, this study aimed was to evaluate the activity of THC, CBD, and their analogs using molecular docking and molecular dynamics simulations (MD) methods. Initially, the molecules (ligands) were selected by bioinformatics searches in databases. Subsequently, CB1 and CB2 receptors were retrieved from the protein data bank database. Afterward, each receptor and its ligands were optimized to perform molecular docking. Then, MD Simulation was performed with the most stable ligand-receptor complexes. Finally, the Molecular Mechanics-Generalized Born Surface Area (MM-PBSA) method was applied to analyze the binding free energy between ligands and cannabinoid receptors. Results: The results obtained showed that ligand LS-61176 presented the best affinity in the molecular docking analysis. Also, this analog could be a CB1 negative allosteric modulator like CBD and probably an agonist in CB2 like THC and CBD according to their dynamic behavior in silico . The possibility of having a THC and a CBD analog (LS-61176) as a promising molecule for experimental evaluation since it could have no central side-effects on CB1 and have effects of CB2 useful in pain, inflammation, and some immunological disorders. Docking results were validate using ROC curve for both cannabinoids receptor where AUC for CB1 receptor was 0.894±0.024, and for CB2 receptor AUC was 0.832±0032, indicating good affinity prediction. Graphical Abstract: ga1 Highlights: Molecular docking, MD simulation, MM-GBSA were performed of cannabinoid derivate of THC and CBD. Of 89 CBD subjected to molecular docking the LS-61176 had the highest affinity score for CB1 and CB2 receptors. LS-67716 behaved in silico during molecular dynamics and MMGBSA similar to CBD-CB1 receptor, and THC-CB2 receptor.